INFLUENCE OF ULTRASONIC TREATMENT ON BACTERIA PRESERVATION DURING SPRAY DRYING OF FERMENTED MILK PRODUCTS - Khmelev V.N.; Shalunov A.V.; Golykh R.N.; Nesterov V.A.; Dorovskikh R.S.; Skiba E.A.; Shavyrkina N.A. (Техника и технология пищевых производств)
High demand for dry fermented milk products determines the relevance of the modernization of drying methods. The existing designs of spray dryers having the highest efficiency are not suitable for drying of fermented milk products because of strict limitations on allowable product temperature (commonly 40 – 45 deg. C) enabling to preserve the viability of microorganisms. The considered in the paper approach to the implementation of a low-temperature spray drying of fermented milk products is characterized by the use of ultrasonic treatment for spraying of raw materials and the interaction between the droplets formed by spraying and the stream of drying agent (air). Ultrasonic spraying of raw materials makes it possible to form an almost monodispersed spray jet (with an average droplet diameter equal to 31 μm), which prevents the entrainment of the product due to the absence of fine fraction and increases the productivity of the process at low temperatures. In turn, the application of ultrasonic vibrations at the stage of interaction between droplets and air intensifies the process of moisture evaporation (by increasing the diffusion coefficient), which makes it possible to reduce the drying temperature to a value not affecting the survival of the bacteria. A result of experimental studies have shown that ultrasonic exposure at spray drying of fermented milk products, both at the stage of spraying and at the stage of interaction of droplets with a stream of the drying agent, does not ensure the survival of microorganisms. Ultrasonic spraying of raw materials in the drying chamber reduces the number of bacteria by more than 10 times because of cavitation. Ultrasonic vibration exposure during evaporation of moisture from the droplets formed by spraying reduces the number of bacteria up to 180 times. The results obtained showed that ultrasonic treatment is not applicable to the spray drying of fermented milk products, but it may be recommended for the drying of thermolabile plant extracts and medicines to remove contaminating microorganisms.